Chemical Characteristics of Banana-Blueberry Velva Product with Various Concentrations of Carboxymethyl Cellulose (CMC) - Jariyah; Isnaini, Yolandra Hibatullah; Defri, Ifwarisan (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
The aim of this research was to analyze the chemical characteristics of Velva products from the mixture of bananas and blueberries with the addition of CMC. This study used a two-factorial completely randomized design with the first factor being the proportion of bananas and blueberries (40:60, 50:50 and 60:40). The second factor was concentration of CMC (0.1, 0.3 and 0.5%). Chemical analysis in this research included total acid, vitamin C, antioxidant activity, crude fiber content, protein, and fat. The data were analyzed by ANOVA using SPSS version 26 with Duncan Multiple Range Test at 5 % probability level. The best results based on the best chemical characteristics were obtained in the treatment of banana and blueberry proportions of (40:60) and CMC concentration of (0.5%) which had characteristics 0.613% total acid, 7.627 mg/100g vitamin C, 42.893% antioxidant activity, 4.450% crude fiber, 3.657% protein and 0.127% fat.